Taxonomic studies of Blachia (Euphorbiaceae) from China (II): B. yaihsienensis is synonymous with B. andamanica, not B. jatrophifolia - Zeng, You-Pai; Zhou, Xin-Xin (Phytotaxa, 2025)
Blachia yaihsienensis (Euphorbiaceae), described from China, has been previously placed in the synonymy of B. jatrophifolia. Critical observations on herbarium specimens (including type material) and living plants in the wild revealed that B. yaihsienensis is actually identical with B. andamanica, not B. jatrophifolia. We therefore reduce B. yaihsienensis to the synonymy of B. andamanica herein. Blachia jatrophifolia thus should be excluded from the flora of China. A distribution map of B. andamanica is provided in this paper.